Recaudación tributaria y su aporte al PIB ecuatoriano por provincias 2010 al 2022 - Guaman Loja, Maria Dolores (2023)
ABSTRACT: The research focuses on the relationship between tax collection and provincial economic growth in Ecuador, adopting a hypothetical-deductive approach with the formulation of a research problem and creation of hypotheses subjected to empirical tests. Econometric models, including fixed and random effects, are used to analyze how taxes (ISD, IR, VAT) are related to the growth of Gross Value Added (GVA) by provinces. The results reveal a positive and statistically significant relationship between taxes and GVA growth, highlighting the importance of tax collection in boosting local economic production. The coherence and significance of the tax coefficients is highlighted, underlining their positive and differential impact on growth. These findings are essential to inform balanced fiscal and economic policies in Ecuador, avoiding excessive tax rates that can hinder investment and development. Consideration of provincial heterogeneity, control for autocorrelation and heteroscedasticity, and the need for ongoing analysis highlight the complexity of this relationship. Ultimately, the results offer valuable guidance for informed decisions and the promotion of equitable and sustainable growth in the country.